Domain-specific c-Myc ubiquitylation controls c-Myc transcriptional and apoptotic activity - Zhang, Qin (National Academy of Sciences, 2013)
The oncogenic transcription factor c-Myc causes transformation and tumorigenesis, but it can also induce apoptotic cell death. Although tumor suppressors are necessary for c-Myc to induce apoptosis, the pathways and mechanisms are unclear. To further understand how c-Myc switches from an oncogenic protein to an apoptotic protein, we examined the mechanism of p53-independent c-Myc–induced apoptosis. We show that the tumor suppressor protein ARF mediates this switch by inhibiting ubiquitylation of the c-Myc transcriptional domain (TD). Whereas TD ubiquitylation is critical for c-Myc canonical transcriptional activity and transformation, inhibition of ubiquitylation leads to the induction of the noncanonical c-Myc target gene, Egr1, which is essential for efficient c-Myc–induced p53-independent apoptosis. ARF inhibits the interaction of c-Myc with the E3 ubiquitin ligase Skp2. Overexpression of Skp2, which occurs in many human tumors, inhibits the recruitment of ARF to the Egr1 promoter, leading to inhibition of c-Myc–induced apoptosis. Therapeutic strategies could be developed to activate this intrinsic apoptotic activity of c-Myc to inhibit tumorigenesis.